2016
DOI: 10.1111/ecc.12442
|View full text |Cite
|
Sign up to set email alerts
|

Training-related improvements in musculoskeletal health and balance: a 13-week pilot study of female cancer survivors

Abstract: Cancer survivors often experience poor post-treatment musculoskeletal health. This study examined the feasibility of combined aerobic and resistant training (CART) for improving strength, skeletal health and balance. Cancer survivors (n = 24) were identified by convenience sampling in Los Angeles County with 11 survivors consenting to 13 weeks of CART. Pre- and post-intervention assessments of bone mineral density (BMD), strength, flexibility and biomarker analysis were performed. Paired t-test analysis sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 129 publications
(185 reference statements)
0
12
0
1
Order By: Relevance
“…These results showed that cancer survivors have impaired body sway function, but it has also been demonstrated that cancer survivors can improve sway velocity in both the eyes open and closed conditions after 13 weeks of combined aerobic and resistance training exercise. 21 Our study suggests that it may be necessary to assess balance function, including TUG time and body sway parameters using a force platform, in order to identify potential loss of balance function in cancer survivors.…”
Section: Discussionmentioning
confidence: 98%
“…These results showed that cancer survivors have impaired body sway function, but it has also been demonstrated that cancer survivors can improve sway velocity in both the eyes open and closed conditions after 13 weeks of combined aerobic and resistance training exercise. 21 Our study suggests that it may be necessary to assess balance function, including TUG time and body sway parameters using a force platform, in order to identify potential loss of balance function in cancer survivors.…”
Section: Discussionmentioning
confidence: 98%
“…Exercise generally has a positive effect on important cancer outcomes including fatigue, urinary incontinence, lymphedema, polyneuropathy, arthralgia, and androgen deprivation related toxicities (Baumann et al, 2015). Almstedt et al (2017) explore dynamic exercise prescription combining aerobic and resistance training, and conclude these kinds of interventions may reduce the risk for falls and fall-related fractures among survivors. Chiu, Hsieh, and Tsai (2017) have conducted a systematic review and concluded that acupuncture has promise as part of a multimodal approach for reducing cancer-related pain.…”
Section: In Our March 2017 Issue Of Ejcc…mentioning
confidence: 99%
“…Almstedt et al. () explore dynamic exercise prescription combining aerobic and resistance training, and conclude these kinds of interventions may reduce the risk for falls and fall‐related fractures among survivors.…”
mentioning
confidence: 99%
“…muscle hypertrophy) in many patients. [18][19][20] However, moderate to high intensity RT may not be suitable for physically frail patients due to the significant cardiorespiratory stress [21][22][23] or after joint surgery due to the high mechanical load. 24 In this regard, alternative therapeutic approaches that may induce lower cardiovascular stress and joint load, while counteracting muscle wasting, in physically frail patients should be considered.…”
mentioning
confidence: 99%